The Case against Forced Methadone Detox in the US Prisons. (19th November 2016) - D'Hotman, Daniel; Pugh, Jonathan; Douglas, Thomas
Abstract: Methadone maintenance therapy is a cost-effective, evidence-based treatment for heroin dependence. In the USA, a majority of heroin-dependent offenders are forced to detox from methadone when incarcerated. Recent research published in The Lancet has demonstrated the negative health and economic outcomes associated with such policies (Rich, J. D., McKenzie, M., Larney, S., Wong, J. B., Tran, L., Clarke, J. et al. (2015). Methadone Continuation Versus Forced Withdrawal on Incarceration in a Combined US Prison and Jail: A Randomised, Open Label Trial. The Lancet, 386, 350–359). This novel evidence raises questions as to the justification for current policies of forced detox in American prisons. Opponents of methadone provision in prisons might offer arguments from retributivism, resource allocation and curative effectiveness to justify their position. This article contends that these arguments do not stand up to ethical scrutiny. In light of this, we hold that American policymakers should reform criminal justice policies to allow the initiation and continuation of methadone treatment in correctional settings. This would be consistent with both international recommendations and the example set by a number of other Western countries.